Slaughter characteristics of Menz and Horro sheep - Ermias, E.; Yami, A.; Rege, J.E.O. (Elsevier, 2006)
Data from 454 Menz and Horro male sheep at Debre Berhan Research Station, Ethiopia, were evaluated for slaughter characteristics. Rams were born from October 1992 to July 1996 and reared together from birth to slaughter at about 17 months of age. Pre-slaughter live weight (PSW) was about 25 kg, while carcass weight (CW) was about 10 kg in both breeds. Empty body weight was significantly higher in the Menz breed than the Horro breed (20.4 kg versus 19.9 kg). The pooled weight of edible non-carcass components in the Menz and Horro sheep was 4.3 and 4.6 kg, respectively. The combined weight of dissected tail and rump fat in the two breeds was about 0.7 kg and 7% of CW. Weights of carcass fat, lean and bone were about 0.9, 6.0 and 2.3 kg, respectively, in the Menz breed and 0.6, 5.9 and 2.5 kg, respectively, in the Horro breed. Fat, lean and bone of the carcass represented about 9, 60 and 23%, respectively, in the Menz and 6, 59 and 25%, respectively, in the Horro. Lean:bone ratio was significantly higher in the Menz than Horro sheep (2.7 versus 2.4). PSW, CW and weights of carcass lean, fat and bone were heritable (0.31-0.51). Heritabilities for carcass lean, fat and bone proportions and lean:bone ratio were estimated at 0.05, 0.49, 0.29 and 0.33, respectively. Genetic correlations among PSW, CW and lean weight were significant (0.83-0.95) indicating selection for PSW should result in a correlated improvement of CW and carcass lean weight. Selection may be beneficial in improving lean:bone ratio, carcass fat and bone proportions in the breeds studied.